A favorable inductive remission rate for decitabine combined with chemotherapy as a first course in <60‐year‐old acute myeloid leukemia patients with myelodysplasia syndrome features. (19th July 2019) - Liu, Fengqi; Wang, Hehua; Liu, Junru; Zhou, Zhenhai; Zheng, Dong; Huang, Beihui; Su, Chang; Zou, Waiyi; Xu, Duorong; Tong, Xiuzhen; Li, Juan
Abstract: In acute myeloid leukemia (AML), myelodysplasia‐related changes contribute to a poor prognosis. This retrospective, propensity score‐matched study analyzed 108 newly diagnosed AML patients with features of myelodysplasia syndrome (MDS) (aged 14‐60 years) from 2014 to 2018, who received either idarubicin and cytarabine (IA) or decitabine, idarubicin and cytarabine (DAC+IA), and compared efficacy and toxicity between the two regimens. After propensity score matching, there were 54 patients in each group. The rate of complete remission (CR) was higher in the DAC+IA group than in the IA group (85.2% vs 68.5%, P  = .040) after the first course, and toxicities were comparable in both groups. Multivariate analysis indicated that the combination with DAC was independent factor for CR rate after the first induction therapy (OR = 2.978, 95% CI:1.090‐8.137, P  = .033). Subgroup analysis showed a CR advantage for DAC+IA (vs IA) for patients of intermediate‐high risk status according to National Comprehensive Cancer Network prognostic stratification. In conclusion, DAC+IA is therefore offered as a new induction choice for newly diagnosed AML patients with features of MDS, aged <60 years old, especially in intermediate‐high risk status. Abstract : Decitabine combined with chemotherapy is therefore offered as a new induction choice for newly diagnosed acute myeloid leukemia patients aged <60 years old, with features of myelodysplasia syndrome, especially in intermediate‐high risk status.